Intrathecal immunoglobulin synthesis in cerebral malaria. - Chapel, H; Warrell, D; Looareesuwan, S; White, N; Phillips, R; Warrell, M; Supawanta, V; Tharavanij, S (1987)
Local synthesis of immunoglobulin within the central nervous system has been evaluated in 37 patients with acute cerebral malaria; seven patients were also studied in the convalescent phase. There was evidence in the cerebrospinal fluid (CSF) of 21 patients that intrathecal IgG synthesis occurs in the acute phase. There were raised IgG: albumin ratios in 43% of acute patients. Oligoclonal IgG bands or cathodal IgG was seen in the CSF of 43% of patients tested by polyacrylamide electrophoresis. Only eight out of 37 acute patients (22%) had no evidence of intrathecal IgG synthesis by either method. The serial studies showed that most patients had IgG-CSF abnormalities when tested in convalescence. These studies suggest that an immune stimulus (perhaps malarial antigens or mitogens) may be present in the brain in acute cerebral malaria.